PENGARUH PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR LQ45 PADA PERIODE 2019-2023 - Muslina Ramadani Iskar; Nurlina Nurlina; Amelia Rezki Septiani Amin (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of working capital turnover on profitability in manufacturing companies incorporated in the LQ45 index on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. This research is a quantitative study using secondary data obtained from the annual financial statements of companies listed on the IDX. The population in this study were 45 companies, with a total sample of 23 companies selected using purposive sampling method based on certain criteria. The data analysis method used is simple linear regression analysis. The results showed that working capital turnover has a significant effect on profitability as measured by Net Profit Margin (NPM). This indicates that the higher the working capital turnover, the higher the level of profitability of the company. This finding implies that the efficiency of working capital management is very important in improving the financial performance of manufacturing companies.